1994
DOI: 10.1111/j.1752-7325.1994.tb01215.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of HIV on VA Dental Services: Report of a Survey

Abstract: While efforts to further reduce the risk of infection and improve care should continue, future efforts also should be directed toward reducing the anxiety of VA dental personnel in the treatment of infectious patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 8 publications
1
2
0
Order By: Relevance
“…Testing for HIV should only be suggested if the degree of protection it affords the oral health care worker is substantially more than the potential harm it may cause the patient (Chikte and Naidoo, 2000). Manz et al (1994) reported that dentists indicated that they felt they should have the right to decide whether to treat people living with HIV and felt they have a professional, rather than a legal obligation to treat people living with HIV (Manz et al, 1994). Similar results were obtained by other researchers where the majority of their participants said they would treat people living with HIV whose needs where within the scope of their practice (Bennet et al, 1995).…”
Section: Introductionsupporting
confidence: 58%
See 1 more Smart Citation
“…Testing for HIV should only be suggested if the degree of protection it affords the oral health care worker is substantially more than the potential harm it may cause the patient (Chikte and Naidoo, 2000). Manz et al (1994) reported that dentists indicated that they felt they should have the right to decide whether to treat people living with HIV and felt they have a professional, rather than a legal obligation to treat people living with HIV (Manz et al, 1994). Similar results were obtained by other researchers where the majority of their participants said they would treat people living with HIV whose needs where within the scope of their practice (Bennet et al, 1995).…”
Section: Introductionsupporting
confidence: 58%
“…Within the resource-stressed setting of a developing country such as South Africa, however, this training and continuing education is not universal. Some dentists consider it their right to refuse treatment to people living with HIV, especially when the risks are high (Barr et al, 1989;Manz et al, 1994;Lapidus and Sandler, 1997), however, refusal to treat a patient after the patient has disclosed their HIV status is discrimination (Chikte and Naidoo, 2000). Current scientific evidence indicates that knowledge of the HIV status of the patient does not provide additional protection to oral health care workers (Naidoo and Govan, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The Questionnaire used for the study was a structured Questionnaire which contained questions pertaining to the knowledge and attitude of the faculty members. The questionnaire was formulated after the review of other questionnaires used in the literature by Aggarwal and Panat [ 17 ], Fotedar et al [ 18 ] and Manz et al [ 19 ] for the assessment of knowledge and attitude among the dental practitioners and dental students. The attitude related questions assessed the willingness of the faculty members towards the dental treatment of HIV/AIDS patients, the potential barriers they perceived and infection control procedures in the treatment of the HIV/AIDS patients.…”
Section: Methodsmentioning
confidence: 99%